Camphor-10-Sulfonic Acid (CSA): A Water Compatible Organocatalyst in Organic Transformations - Brahmachari, Goutam; Nurjamal, Khondekar; Karmakar, Indrajit; Mandal, Mullicka (Current Organocatalysis, 2018)
In recent times, organocatalysis has received considerable attention of the chemical community due to its multifaceted benefits in organic synthesis, and is regarded as one of the hot research topics in advanced organic chemistry. Organocatalysts offer an alternative platform to the conventional transition metal catalysis, thereby satisfying several green chemistry aspects. Organocatalytic reactions have already emerged as powerful tools in the construction of simple to complex molecular scaffolds, and this research field of topical interest is developing fast with newer concepts. During the recent past, camphor-10-sulfonic acid, commonly known as CSA, has served as a promising organocatalyst in performing a huge array of organic transformations. CSA is relatively safe, commercially available, and cheap. The present review, for the first-time, offers an up-to-date literature on the developments of CSA-catalyzed organic transformations.
Keywords: organocatalysis